1980
DOI: 10.3382/ps.0592165
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoid Leukosis Virus Infection: Effects on Production and Mortality and Consequences in Selection for High Egg Production

Abstract: Lymphoid leukosis (LL) is virus-induced, lymphoblastic malignancy of chickens that can be congenitally transmitted. Mortality from LL is generally low. Effects of LL virus (LLV) on production and mortality were investigated in approximately 2000 Leghorn pullets in each of two consecutive years. The pullets were from nine strains developed in Ottawa, of which three were unselected control strains and six were strains under selection for up to 27 generations for high egg production and a complex of related comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
3

Year Published

1982
1982
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 15 publications
4
36
3
Order By: Relevance
“…The benefits expected from such programmes are the prevention of losses from leukosis and non-neoplastic disorders and improved performance (Gavora et al, 1980;. This method of disease prevention has become feasible as a result of two developments (1) recognition that hens that produce congenitally infected chicks have LLV in vaginal swabs or in their egg albumen, and (2) improvements in the techniques available for large scale testing for LLV (Spencer et al, 1977;Clark et al, 1981 ;Fadly et al, 1981 ;Payne et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The benefits expected from such programmes are the prevention of losses from leukosis and non-neoplastic disorders and improved performance (Gavora et al, 1980;. This method of disease prevention has become feasible as a result of two developments (1) recognition that hens that produce congenitally infected chicks have LLV in vaginal swabs or in their egg albumen, and (2) improvements in the techniques available for large scale testing for LLV (Spencer et al, 1977;Clark et al, 1981 ;Fadly et al, 1981 ;Payne et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…Under field conditions LLV-A is the most common agent; it induces lymphoid leukosis at a low mortality rate (5%), and also reduces the overall performance of the flock because of reduced hen-housed egg production, delayed sexual maturity, poor yolk index and, above all, a significantly higher percentage of non-specific deaths (Spencer et al, 1978(Spencer et al, , 1979Gavora et al, 1980;Garwood et al, 1981;Payne et al, 1982;Romero et al, 1983). These research reports have aroused considerable interest amongst commercial poultry breeders in eradicating LLV-A from chicken flocks in order to improve their performance.…”
Section: Pjcpaniefc/mentioning
confidence: 99%
“…It has been shown previously (Spencer et al, 1979) that there is good agreement between the tests for the gs antigen and LLV. The fact that gs antigen is shed into egg albumen with a high degree of consistency is documented by the good agreement between tests on eggs collected from the same hens around 250 and 470 days of age (Gavora et al, 1980). Cloacal swabs were obtained from the 42-day-old crosses of the primary breeding stocks hatched in 1979 and they were used for detection of LLV by the phenotypic mixing test (Okazaki et al, 1975).…”
Section: Tests For Ll V Infectionmentioning
confidence: 99%
“…Recently, however, Gavora et al (1980) reported that egg production was significantly reduced (25 to 30 eggs per hen housed) in Leghorn hens shedding LL virus (LLV) into eggs. This reduction resulted from later sexual maturity, higher mortality from causes other than LL, and lower egg production rate.…”
Section: Introductionmentioning
confidence: 99%